Incertidumbre en la disponibilidad de recursos hídricos superficiales en la Cuenca del Ebro: análisis temporal desde una perspectiva plurisecular - Saz Sánchez, Miguel Ángel; Vicente-Serrano, Sergio M. (Geographicalia, 2016)
Using dendroclimatic reconstructions of annual precipitation in Capdella (Central-Eastern Pyrenees) and Pallaruelo de Monegros (Central Ebro Valley), rainfall evolution in Ebro Valley since 16th century is analyzed. These reconstructions show precipitation fluctuations in both climatic areas. The main anomalies occur in 16th and 17th centuries, during Little Ice Age, as well as in the second half of 20th century. Furthermore, dendroclimatic reconstructions allow LIS to evaluate some probabilistic analysis applied in hydrologic rnanagement.